Transformasi Ruang Diskusi Publik Program Beladas Radio Elshinta Palembang - Ilham Adriyan; Muhammad Ravi Aziz Anafi; Dody Kusuma Jaya; Abdur Razzaq; Muhammad Yudistira Nugraha (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The transformation of the public discussion space on Radio Elshinta Palembang's Beladas program demonstrates a shift in community communication patterns from mere information consumption to active two-way interaction. This study aims to determine how the Beladas program plays a role in strengthening public participation and serving as a platform for community dialogue. The research method used was descriptive qualitative, with data collection techniques including interviews, observation, and documentation. The research subjects included broadcasters, local communities, and active listeners of the Beladas program. The results indicate that the program is able to provide an inclusive dialogue space and encourage active community involvement in addressing important issues. Beladas is also considered capable of bridging communication between various communities, improving media literacy, and strengthening the role of radio as a traditional medium that remains relevant in the digital age. However, challenges such as adapting to digital platforms and limited online interaction remain obstacles. In conclusion, the Beladas program can be an effective interactive broadcast model for building public discussion spaces at the local level. The transformation of the public discussion space on Radio Elshinta Palembang's Beladas program demonstrates a shift in community communication patterns from mere information consumption to active two-way interaction. This study aims to determine how the Beladas program plays a role in strengthening public participation and serving as a platform for community dialogue. The research method used was descriptive qualitative, with data collection techniques including interviews, observation, and documentation. The research subjects included broadcasters, local communities, and active listeners of the Beladas program. The results showed that this program was able to provide a space for inclusive dialogue and encourage active community involvement in addressing important issues. Beladas was also deemed capable of bridging communication between various communities, increasing media literacy, and strengthening the role of radio as a conventional medium that remains relevant in the digital age. However, challenges such as adapting to digital platforms and limited online interaction remain obstacles. In conclusion, the Beladas program can be an effective interactive broadcast model for building public discussion spaces at the local level.